(untitled) (Revista Apotheke, 2025)
This cartography investigates the relationship between the space of the studio-house and the creative process of artists who share, in the same environment, their experiences of living and artistic work. The study includes interviews with the Santa Catarina-based artists Celaine Refosco and Nara Guichon, as well as photographic records of their spaces, aiming to understand how modes of inhabiting influence artistic production and how the boundaries between everyday life and artistic practice intertwine in this context. The research proposes to reflect on how the house offers a privileged intimacy for the construction of the artwork, while at the same time it may emerge as a solution motivated by economic needs. The studio-house at times merges its forms and limits with the artwork itself, and vice versa, establishing itself as a place of mutual construction, rather than merely as a backdrop or functional support for artistic production.